Determinants of V̇+O2peak Changes After Aerobic Training in Coronary Heart Disease Patients - Girault, Axel; Leprêtre, Pierre-Marie; Trachsel, Lukas-Daniel; Besnier, Florent; Boidin, Maxime; Lalongé, Julie; Juneau, Martin; Bherer, Louis; Nigam, Anil; Gayda, Mathieu (International Journal of Sports Medicine, 2024)
This study aimed to highlight the ventilatory and circulatory determinants of changes in ˙VO2peak after exercise-based cardiac rehabilitation (ECR) in patients with coronary heart disease (CHD). Eighty-two CHD patients performed, before and after a 3-month ECR, a cardiopulmonary exercise testing (CPET) on a bike with gas exchanges measurements (˙VO2peak, minute ventilation, i. e., ˙VE), and cardiac output (Q˙c). The arteriovenous difference in O2 (C(a-v¯)O2) and the alveolar capillary gradient in O2 (PAi-aO2) were calculated using Fick’s laws. Oxygen uptake efficiency slope (OUES) was calculated. A 5.0% cut off was applied for differentiating non- (NR: ˙VO2<0.0%), low (LR: 0.0≤ ∆˙VO2<5.0%), moderate (MR: 5.0≤∆˙VO2 < 10.0%), and high responders (HR: ∆˙VO2≥10.0%) to ECR. A total of 44% of patients were HR (n=36), 20% MR (n=16), 23% LR (n=19), and 13% NR (n=11). For HR, the ˙VO2peak increase (p<0.01) was associated with increases in ˙VE (+12.8±13.0 L/min, p<0.01), (+1.0±0.9 L/min, p<0.01), and C(a-v¯)O2 (+2.3±2.5 mLO2/100 mL, p<0.01). MR patients were characterized by+6.7±19.7 L/min increase in ˙VE (p=0.04) and+0.7±1.0 L/min of Q˙c (p<0.01). ECR induced decreases in ˙VE (p=0.04) and C(a-v¯)O2 (p<0.01) and a Q˙c increase in LR and NR patients (p<0.01). Peripheral and ventilatory responses more than central adaptations could be responsible for the ˙VO2peak change with ECR in CHD patients.
Keywords: coronary heart disease; exercise based cardiac rehabilitation; limiting O2 factors; non-invasive measurements